The influence of impurities on the saturated vapor pressure hydrocarbon media - Степанов, М.Б.; Дрогобицька, І.В.; Ледовських, В.М. (Proceedings of National Aviation University (archive), 2009)
Here are presented experimental result due to the research of the impact non – volatile admixture on the pressure of saturated steam of Hydrocarbonic medium. It is showed, that in their presence is watched the positive deflection from ideal state due to the Raul's low. Also is watched an appropriate decrease of the quantity of positive deflection of saturated steam from Raul's law in Hydrocarbonic consequence C6H14 - C13H28 – C16H34,, which could be explained by increasing of depressive intermolecula cooperation energy with increasing of molecule's possibility to polarize.